ANALISIS PENDAPATAN USAHATANI KENTANG DI DESA SINSINGON KECAMATAN PASSI TIMUR KABUPATEN BOLAANG MONGONDOW - Ferry Runturambi; Rine Kaunang; Theodora Maulina Katiandagho (AGRI-SOSIOEKONOMI, 2020)
This study aims to analyze the income of potato farming in Sinsingon Village, Passi Timur District, Bolaang Mongondow Regency. This research was conducted in Sinsingon Village, Passi Timur District, Bolaang Mongondow Regency. Sampling in this study was carried out by simple random sampling, as many as 30 farmers who worked on potatoes. This research uses primary and secondary data. Primary data collection was carried out by direct interview with potato farmers in Sinsingon Village. Secondary data were collected from the Sinsingon Village Office and Passi Timur Sub-district Agriculutural Extension Office. Data analysis uses the formula for income and R / C ratio. The results showed that the average potato farm receipts per farmer was Rp. 18,746,000 and the total average cost per farmer is Rp. 10,891,458.33 and produce an average income per farmer of Rp. 7,854,541.67 so as to obtain an R / C ratio of> 1 which is 1.72, it means that the potato farming in Sinsingon Village, Passi Timur District is experiencing profit so that this business is worth the effort.*eprm*